Evaluating the Causes of Land Subsidence in Central Jakarta using 1-Dimensional Consolidation Approach - Naufal, Muhammad Adi; Sadisun, Imam Achmad; Kartiko, Rendy Dwi; Septiandi, Muhammad Iqbal (Jurnal Ilmiah Geologi PANGEA, 2024)
Land subsidence in Central Jakarta, driven by both natural geological processes and human-induced factors, threatens the stability of the region’s infrastructure. Monitoring of land subsidence with InSAR in Central Jakarta shows an average speed of 1-10 cm/year. Land subsidence in Central Jakarta presents a growing geotechnical challenge, exacerbated by both natural consolidation and anthropogenic influences. During the period of 2018 to 2023, Jakarta's booming industrial development became a major factor contributing to the city's ongoing land subsidence problem. This study aims to evaluate the contribution of consolidation and anthropogenic factors to land subsidence in Central Jakarta. The analytical method uses 1-D consolidation theory is applied to calculate land subsidence. Borehole data from nine locations were used to estimate subsidence rates. Results indicate that natural consolidation has significant role in land subsidence, which is predicted to continue until 2368. Anthropogenic factors such as groundwater level decrease and additional building loads accelerate the subsidence process. The rate of soil subsidence for natural consolidation in Central Jakarta ranges from 1.5-9.1 cm/year. Meanwhile, there are anthropogenic factors such as groundwater level decrease and increase of building load achieved 3.4-17.4 cm/year. These anthropogenic factors accelerate the rate of soil subsidence by 1.9-8.3 cm/year or equivalent to 26.0-47.7%. Based on analysis, land subsidence analysis in Central Jakarta shows that increase in building load and groundwater level decrease in five years does not significantly affect the subsidence that occurs. However, role of anthropogenic factors can exacerbate land subsidence in Central Jakarta. Groundwater extraction arrangements and building load management need to be considered to minimize the negative impact on infrastructure.